Identification of volatile compounds from myiasis wounds and its responsesfor Chrysomya bezziana - April H Wardhana; Sukarsih .; R Urech (Jurnal Ilmu Ternak dan Veteriner, 2005)
Development of attractant for screwworm fly was required in myiasis control on livestock. The purpose of this study is to identify of volatile compounds from myiasis wound infested with Chrysomya bezziana larvae including to assess their responses in both cage and room assays. Both Friesian-Holstein heifer (FH) (animal 1) and Bali cattle (animal 2) were used as myiasis model. The artificial wounds (8-10 cm) were conducted on the rump of both animals and infested with about 200 eggs of C.bezziana. Odours from the infested wound were collected on day 1 and 3 for animal1 and day 3 and 5 for animal 2, post C. bezziana larvae infestation. Two different collection devices were used: firstly, absorption onto Tenax kept in steel tubes, whichwas attached to a collected bowl. The volatile organic compounds were collected from the wound and the surrounding animal hide by flowins the air through the inlet and outlet. Secondly, a solid phase micro extraction (SPME) device was inserted into bowl with passive (no air flow) odour collection. Gass chromatography/mass spectrometry was used to identify volatile compounds from wound. The compounds of the wound on animal 1, collected on day 1, produced only minor quantities of compounds (nonanal, decanal, hexanal and heptanal). Minor components such as DMDS and DMTS were only detected on day 3. The compounds of the wound on animal 2 was more varied and had a peculiar strike-like smell on day 3 and 5. They included indole, phenol, acetone, various sulfides (DMS, DMDS, DMTS), alcohols (butanol, 3-methylbutanol), aldehydes and acids. These compounds were selected and formulated into attractant (B92) then tested in both cage and room assays using SL-2 as control. Respond of flies was analyzed by ANOVA 5% (cage assay) and T test 5% (room assay). The result showed that the fly response to B92 was very low compared to SL-2 in cage assays (P<0.05). The addition of B92 to SL-2 could not increase the catch of flies in the cage assays (SL-2+B92=10:1; 10:3), there was no difference between SL-2 and B92/SL-2 in room assay, the fly response still low (P>0.05).     Key Words: Volatile Compound, Myiasis, Wound, Chrysomya bezziana